THE INFLUENCE OF WAVE PATTERNS AND FREQUENCY ON THERMO-ACOUSTIC COOLING EFFECT - CHEN BAIMAN; MUSHTAK AL-ATABI; YOUSIF A. ABAKR (Journal of Engineering Science and Technology, 2011)
With the increasing environmental challenges, the search for an environmentally benign cooling technology that has simple and robust architecture continues. Thermo-acoustic refrigeration seems to be a promising candidate to fulfil these requirements. In this study, a simple thermo-acoustic refrigeration system was fabricated and tested. The thermo-acoustic refrigerator consists of acoustic driver (loudspeaker), resonator, stack, vacuum system and testing system. The effect of wave patterns and frequency on thermo-acoustic cooling effect was studied. It was found that a square wave pattern would yield superior cooling effects compared to other wave patterns tested.